The Application of Role Playing Method in the Digestive System Material Learning in SMPN 4 Geyer - Susilo, Barep Purbo; Kartijono, Nugroho Edi; Purwantoyo, Eling (FMIPA UNNES, 2020)
This research purposes to know students activity and learning result in the application of Role Playing in the digestive system material. The study used Pre- Experimental One-Shot Case Study design. The population of the study is all students of grade VIII of SMP N 4 Geyer. The sample of the study is VIII B and VIII E and use Simple Random Sampling method to choose the sample. The observation results of the students’ activity from both classes are 91.7% and 88.5% with good and very good category. The learning outcomes on knowledge and skill aspects from both classes are 95.8% and 88.4% students are included in good and very good category. The classical completeness is 95.8% and 92.3%. The teacher and students’ response show positive respond toward the applied learning method.